Impact of viral load at admission on the development of respiratory failure in hospitalized patients with SARS-CoV-2 infection - de la Calle, Cristina (Eur J Clin Microbiol Infect Dis, 2021)
The aim of our study was to elucidate if SARS-CoV-2 viral load on admission, measured by real-time reverse transcriptase–polymerase chain reaction (rRT-PCR) cycle threshold (Ct) value on nasopharyngeal samples, was a marker of disease severity. All hospitalized adult patients with a diagnosis of SARS-CoV-2 infection by rRT-PCR performed on a nasopharingeal sample from March 1 to March 18 in our institution were included. The study population was divided according to the Ct value obtained upon admission in patients with high viral load (Ct < 25), intermediate viral load (Ct: 25–30) and low viral load (Ct > 30). Demographic, clinical and laboratory variables of the different groups were analyzed to assess the influence of viral load on the development of respiratory failure during admission. Overall, 455 sequential patients were included. The median Ct value was 28 (IQR: 24–32). One hundred and thirty patients (28.6%) had a high viral load, 175 (38.5%) an intermediate viral load and 150 (33%) a low viral load. Advanced age, male sex, presence of cardiovascular disease and laboratory markers such as lactate dehydrogenase, lymphocyte count and C-reactive protein, as well as a high viral load on admission, were predictive of respiratory failure. A Ct value < 25 was associated with a higher risk of respiratory failure during admission (OR: 2.99, 95%IC: 1.57–5.69). SARS-CoV-2 viral load, measured through the Ct value on admission, is a valuable tool to predict the development of respiratory failure in COVID-19 inpatients. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10096-020-04150-w.